2021
DOI: 10.1097/md.0000000000023905
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of routine ultrasonography combined with ultrasound elastography for papillary thyroid microcarcinoma

Abstract: Background: Papillary thyroid microcarcinoma is easy to be missed because of its small focus, concealed incidence and lack of clinical features. Ultrasound examination is one of the main methods for the detection and diagnosis of papillary thyroid microcarcinoma. The detection rate of conventional ultrasound is not ideal. Combined ultrasound elastography can improve the detection rate, but there is lack of evidence-based evidence. The purpose of this study was to systematically evaluate the value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…An accurate differential diagnosis can avoid unnecessary FNA or surgery for benign nodules. Hu [11] 2013 China a Prospective 51/57 20/31 47.4 ± 12.2 SonoVue (1.2 mL) c or d Chen et al [12] 2014 China a Prospective 216/258 49/167 NA SonoVue (1.0-1.2 mL) c Yan et al [13] 2014 China a Prospective NA/138 NA NA SonoVue (1.2 mL) c Li et al [8] 2015 China a Retrospective 73/80 21/52 39.5 ± 11.3 SonoVue (2.4 mL) c Wang et al [14] 2015 China a Prospective 98/109 30/68 44.8 ± 10.8 SonoVue (NA) c Yang [15] 2016 China a Retrospective 69/107 14/55 45.5 ± 8.4 NA c Ma et al [16] 2016 China a Prospective 125/135 NA 48.6 ± 12.0 SonoVue (2.4 mL) c Xu et al [17] 2017 China a Prospective 161/175 29/132 46.2 ± 15.2 SonoVue (2.5 mL) c or d Xu et al [18] 2017 China a Prospective 59/85 22/37 46.5 ± 3.3 SonoVue (NA) c or d Li [19] 2018 China a Prospective 154/185 27/127 48.7 ± 12.8 SonoVue (2.0 mL) c or d He et al [20] 2018 China a Prospective 496/564 228/268 39.2 ± 11.6 SonoVue (1.8 mL) c Jia [21] 2018 China a Retrospective 100/113 31/69 44.8 ± 9.8 SonoVue (2.4 mL) c Hao et al [22] 2019 China a Prospective 97/107 54/43 45.3 ± 3.7 SonoVue (NA) c Ci [23] 2019 China a Prospective 161/183 53/108 43.9 ± 11.1 SonoVue (2.4 mL) c Huang et al [24] 2019 [26] 2022 China b Prospective 45/60 14/31 47.6 ± 14.7 SonoVue (2.0 mL) c Tu [27] 2020 China a Prospective 40/58 16/24 48.2 ± 3.7 SonoVue (2.4 mL) c Wu [28] 2020 China a Prospective 60/60 19/41 50.0 ± 7.8 SonoVue (1.5 mL) c Liu et al [29] 2020 China a Retrospective 98/109 53/45 45.7 ± 8.1 SonoVue (NA) c or d Li [30] 2020 China a Prospective 75/93 29/46 38.7 ± 10.1 SonoVue (2.4 mL) c Peng and Cheng [31] 2020 China a Prospective 92/108 36/56 42.6 ± 10.6 NA (1.0 mL) c or d Zhang [32] 2020 China a Prospective 80/80 36/44 46.5 ± 5.8 Gd-DTPA (NA) c Liang [33] 2020 China a Prospective 106/106 NA NA NA (5.0 mL) c Wu et al [34] 2021 China a Retrospective 98/105 33/65 39 (18-67) SonoVue (2.0 mL) c Chen and Li [35] 2021 China a Prospective 65/74 25/40 42.0 ± 12.1 SonoVue (1.5 mL) c Zheng et al [36] 2021 China a Retrospective 92/106 40/52 45.0 ± 2.2 SonoVue (1.5 mL) c Li [37] 2021 China a Prospective 115/128 18/97 46.3 ± 6.5 SonoVue (2...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An accurate differential diagnosis can avoid unnecessary FNA or surgery for benign nodules. Hu [11] 2013 China a Prospective 51/57 20/31 47.4 ± 12.2 SonoVue (1.2 mL) c or d Chen et al [12] 2014 China a Prospective 216/258 49/167 NA SonoVue (1.0-1.2 mL) c Yan et al [13] 2014 China a Prospective NA/138 NA NA SonoVue (1.2 mL) c Li et al [8] 2015 China a Retrospective 73/80 21/52 39.5 ± 11.3 SonoVue (2.4 mL) c Wang et al [14] 2015 China a Prospective 98/109 30/68 44.8 ± 10.8 SonoVue (NA) c Yang [15] 2016 China a Retrospective 69/107 14/55 45.5 ± 8.4 NA c Ma et al [16] 2016 China a Prospective 125/135 NA 48.6 ± 12.0 SonoVue (2.4 mL) c Xu et al [17] 2017 China a Prospective 161/175 29/132 46.2 ± 15.2 SonoVue (2.5 mL) c or d Xu et al [18] 2017 China a Prospective 59/85 22/37 46.5 ± 3.3 SonoVue (NA) c or d Li [19] 2018 China a Prospective 154/185 27/127 48.7 ± 12.8 SonoVue (2.0 mL) c or d He et al [20] 2018 China a Prospective 496/564 228/268 39.2 ± 11.6 SonoVue (1.8 mL) c Jia [21] 2018 China a Retrospective 100/113 31/69 44.8 ± 9.8 SonoVue (2.4 mL) c Hao et al [22] 2019 China a Prospective 97/107 54/43 45.3 ± 3.7 SonoVue (NA) c Ci [23] 2019 China a Prospective 161/183 53/108 43.9 ± 11.1 SonoVue (2.4 mL) c Huang et al [24] 2019 [26] 2022 China b Prospective 45/60 14/31 47.6 ± 14.7 SonoVue (2.0 mL) c Tu [27] 2020 China a Prospective 40/58 16/24 48.2 ± 3.7 SonoVue (2.4 mL) c Wu [28] 2020 China a Prospective 60/60 19/41 50.0 ± 7.8 SonoVue (1.5 mL) c Liu et al [29] 2020 China a Retrospective 98/109 53/45 45.7 ± 8.1 SonoVue (NA) c or d Li [30] 2020 China a Prospective 75/93 29/46 38.7 ± 10.1 SonoVue (2.4 mL) c Peng and Cheng [31] 2020 China a Prospective 92/108 36/56 42.6 ± 10.6 NA (1.0 mL) c or d Zhang [32] 2020 China a Prospective 80/80 36/44 46.5 ± 5.8 Gd-DTPA (NA) c Liang [33] 2020 China a Prospective 106/106 NA NA NA (5.0 mL) c Wu et al [34] 2021 China a Retrospective 98/105 33/65 39 (18-67) SonoVue (2.0 mL) c Chen and Li [35] 2021 China a Prospective 65/74 25/40 42.0 ± 12.1 SonoVue (1.5 mL) c Zheng et al [36] 2021 China a Retrospective 92/106 40/52 45.0 ± 2.2 SonoVue (1.5 mL) c Li [37] 2021 China a Prospective 115/128 18/97 46.3 ± 6.5 SonoVue (2...…”
Section: Discussionmentioning
confidence: 99%
“…Figure 10. Influence analysis was described to show that 4 original studies had strong influence, and other studies would not cause influence to the results (8 = Xu et al [17] ; 14 = Ci [23] ; 15 = Huang et al [24] ; 30 = Ge and Li [39] ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that thyroidectomy and lymph node dissection can achieve good treatment outcomes for patients with early PTMC lymph node metastasis. Nevertheless, misdiagnosis and missed diagnosis are prone to occur when utilizing palpation to diagnose small-volume lymph node metastasis, which often delays optimal time for therapy [4]. Thus, elevating accuracy of early diagnosis in PTMC is crucial.…”
Section: Introductionmentioning
confidence: 99%